MIG/MAG kaynağında bilgisayar yardımıyla maliyet hesabı - Yalazan, Kadri (Fen Bilimleri Enstitüsü, 1996)
Yapılan bu çalışmada MIG/MAG kaynak dikişi maliyet hesabı incelenmiştir. Ayrıca bu hesabı veren BASIC dilinde bir bilgisayar programı da yazılmıştır. Çalışmanın ilk bölümü bir giriş mahiyetinde olup bu bölümde MIG/MAG kaynağının kısaca tarihi gelişimine ve maliyet hesabının önemine değinilmiştir. İkinci bölümden itibaren MIG/MAG kaynak donanımı, koruyucu gazlan, kaynak elektrodları ve parametre seçimi hakkında bilgi verilmiştir. Son bölümde uzman sistemler ve MIG/MAG kaynak dikişi maliyet hesabı verilmiştir. Maliyete etki eden faktörler incelenip gereken formüller kullanılarak bir maliyet hesabı yapılmış ve bir kaç örnek gösterilmiştir.

Gas metal arc welding (GMAW) is an electric arc welding process which produced caalescense of metals by heating them with an arc established between a continuous filler metal (consumable) electrode and the work. Shielding of the arc and molten weld pool is obtained entirely from an externally supplied gas or gas mixture. The process in sometimes referred to as MIG or C02 Welding (MAG). When GMAW was first developed, it was considered to be fundamentally a high current density, small diameter, bare metal electrode process using an inert gas for arc shielding. Its primary application was for welding aluminum. As a result, the term MIG (Metal Inert Gas) was used and is still the most common reference for the process. Subsequent developments include operation at low current densities and pulsed direct current, application to a broader range of materials, and the use of reactive gases (particularly CO2) or gas mixtures. This latter development has led to the formal acceptance of the term gas metal arc welding (GMAW) for the process because both inert and reactive gases are used. [4] GMAW is operated in semiautomatic machine, and automatic modes. It is utilized particularly in high production welding operations. All commercially important metals such as carbon steel, stainless steel, aluminum, and copper can be welded with this process in all positions by choosing the appropriate shielding gas, electrode, and welding conditions. The consumables used in GMAW are electrodes and shielding gases. The chomical composition of the electrode, in combination with the shielding gas, will influence the weld metal composition which determines the chemical and mechanical properties of the weldment. Factors influencing the selection of the shielding gas wire electrode combination are 1. Base metal composition 2. Base metal mechanical properties 3. Base metal condition and cleanliness 4. Type of service or applicable specification requirement 5. Welding position 6. Type of filler metal transfer (spray, globular, or short circuiting) The electrodes for gas metal arc welding are usually quite similar or identical in composition to those used for welding with most other bare electrode process. As a rule, the compositions of the electrode and the base metal are as nearly alike as practicable, commensurate with good welding characteristics and well properties. In some cases, this involves very little modification from the base metal composition. In X other cases, obtaining satisfactory welding and weld metal characteristics requires an appreciable composition change, perhaps the use of an electrode of completely different compositon. For example, the electrode that are most satisfactory for welding manganese bronze, a copper - zinc alloy are either aluminum bronze or copper - manganese - nickel - aliminum alloys. Somewhat similarly, although not to the same degree, the electrodes that are most suitable for welding the higher strength aluminum and steel alloys are usually quite different in composition from the base metal on which they are to be used. This is because some alloys, such as 6061, that are quite satisfactory or desirable as base metals are unsuitable as weld metal. Accordingly, electrode alloys are designed to produce the desired weld metal properties and the acceptable operating characteristics. When molten, most metal combine with the basic elements in air, oxygen and nitrogen, to form metal oxides and nitrides. Contamination of the weld metal can result in low strength, low ductility, and excessive weld defects such as porosity and lack of fusion. The primary purpose of the shielding gas in gas metal arc welding is to protect the molten weld metal from contamination and damage by the surrounding atmosphere. Most spray type GMAW is done in the flat position, while pulsed and short circuiting GMAW can be used in all positions. Fillet welds made in the flat position with spray transfer are usually more uniform, less likely to have unequal legs and convex profiles, and less susceptible to undercutting than similar fillet welds made in the horizontal position. The welding procedures for GMAW are similar to those for other arc welding processes. Adequate fixturing and clamping of the work are required with adequate accessibility for the welding gun. Fixturing must hold the work rigid to minimize distortion from welding. It should be designed for easy loading and unloading. Good connection of the work lead (ground) to the work-piece or fixturing is required. Location of the connections is important, particularly when welding ferromagnetic materials such as stell. Generally the best direction of welding is away from the work lead connection. The position of the electrode with respect to the weld joint is important in order to obtain the desired joint penetration, fusion, and weld bead geometry. Elecrode positions for automatic GMAW are similar to those used with submerged arc welding. Welding costs are usually derived by considering three cost categorise, materials, labor and overhead (electricity... etc) [4] Materials : These items are considered the consumables of the process, they include the wire electrode and shielding gas. wire costs per unit weight are dependent on the elecrode diameter, type of alloy, size of package, and quantitiy purchased. Small diameter wire electrodes, such as those used for gas metal arc and gas tungsten arc welding, are more costly than the larger diameter wires used for submerged arc welding. Flux cored electrodes are usually more costly than solid wire electrodes because they are fabricated wire electrodes containing flux. XI Shielding gas is another consumable expense associated with GMAW, mert gas or gas mixtures are used for both ferrous and nonferreus materials, but they are higher priced than carbon dioxide (CO2) which has found wide use for carbon and low alloy steel fabrication. Liquefied gas distribution systems within a plant offer considerable savings over individual high pressure gas cylinders when they can be justified for volume production. Submerged arc welding, which does not require a gas shield, uses a granular flux distributed over the weld zone immediately prior to welding. On the average, every pound of wire deposited consumes a pound of flux. Materials costs are also influenced by the inherent efficiency of each process in depositing metal. Estimates have been made of the deposition efficiency for each of the major consumable electrode processes. These values reflect the electrode losses in such froras as metal vapor, slag, spatter, and unusable electrode (stub) losses. Labor: Generally, direct labor is the dominant cost factor in any welding operation. The labor costs of welders or welding operators are a direct function of the travel speed of the process and the operating factor or duty cycle involved. The operating factor is the ratio of the actual arc time to the total time. There is considerable difference between welding processes with respect to travel speeds. For instance, shielded metal arc welding can possibly be done at a maximum of approximately 20 mm/s, while gas metal arc welding can be done at welding speeds of 65 to 85 mm/s, or more. The operating factor is reduced by any operation that decreases arc time, such as frequent electrode replacement and the removal of fused slag or spatter. All three operations are associated with shielded metal arc welding, while submerged arc welding requires only fused slag removal. Depending on the application and shielding gas used, only the removal of spatter may be required with GMAW. In gneeral,the use of this process results in one of the highest operating factors. Overhead: Items such as ancillary facilities, services and utilizes necessary for porduction welding are included in the overhead. The amortization of capital equipment used for welding is also considered an overhead expense. The power source and associated equipment used for shielded metal arc welding are the least complicated, and therefore the least expensive of all the arc welding processes. Both semiautomatic gas metal arc and flux cored arc welding require an electrode wire feeder and a more elaborate delivery system (gun with shielding gas flow). Consequently, the amortization expenses are greater. Submerged arc welding and the automatic versions of gas metal arc and flux cored are welidng equipment, with their associated controls and guidance fixtures, increase the overhead even more. For almost a decade, computer programs have been written specificilly as aids for the welding engineer. There are now some one-hundrend programs available and many companies can be classed as frequent users of welding engineering packages. The programs include both equipment control software and stand-alone application packages for use with the personal computer. It is, therefore, timely to review the range of commercially available programs with the intention of establishing the scope and features of both the industry established and the more recently produced packages. The review is restricted to information and knowledge based packages xn which are PC based, but excludes the more specialised programs such as manufacturing simulation tools. [12] When describing the more recently produced packages, the opportunity is taken to highlight those established packages which have recently been enhanced to take account of the increasing responsibilities of the welding engineer. The trend in company software is to co-ordinated packages, which not only facilitate the transfer of data between programs but also make it easier for engineers of other disciplines to access the data. With regard to new packages, novel programming techniques have been exploited to extend the range of subject areas. Here, it is considered that expert systems and multimedia based software will have an important role to play in producing the next generation of packages. Welding engineering software: PC based, welding engineering software is very wide ranging, from simple calculation programs to sophisticated packages containing expert knowledge. The programs can be conveniently categorised into following subject areas: - Storage of information. - Repetitive calculations. - Interpretation of standards. - Encapsulation of expert knowledge. - Training. - Marketing. In terms of sales, the storage of information based packages are the most popular, whilst there are relatively few training and marketing programs sold. However, it should be noted that most of these latter packages have been written as company-specific products and are not generally produced as 'off the shelf ' packages. -Storage of information, Welding procedures, welder qualifications, NDT records, consumables, welding records. -Repetitive calculations, Weld volumes, consumable requirements, cost of fabrication, design assessment, fatigue service. -Interpretation of standarts, Preheat requirements, post-weld heat treatment, fatigue calculations, welding procedure checking. -Encapsulation of expert knowledge, XIII Diagnosis of weld cracks, process selection, shielding gas selection welding parameters -Training Fume generation, distortion control, distance learning, EWF. -Marketing Shielding gas selection, consumable selection. Welding engineering packages have now been available commercially for almost a decade and several thousand packages have been sold by TWI worldwide. The range of subject areas is extensive, covering all branches of welding from desing to the solution of fabrication problems. However, apart from those programs which have been designed for use on a day to day basis in companies, eg, welding procedure databases, their use by welding engineers, as reflected in sales, remains relatively small. Several reasons have been put forward to account for the relative low usage, including their specialist nature, high cost and the general computer literacy of welding engineers. The specialist nature of some of the software, such as an expert system to diagnose the cause of weld cracks during fabrication, means that the package will be used quiete infrequently, possibly as little as once every mounth. This raises the question as to whether it is easier to consult a specialist welding engineer, rather than to load the package and become familiar with its operations. The relatively high cost of the packages reflects their specialist nature and their high production costs. Apart from the databases and calculation packages, many of those available commercially will not recover their production costs because of the low sales. Expert systems, in particular, are elegant tools for encapsulating specialist expertise, but will almost certainly not be produced in any great number. These types of packages are extremely expensive to produce because they require a substantial investment in the amount of effort to be devoted to collating data, interviewing the expert and the validation of the program. Large companies may continue to invest in these technologies as a means of preserving their inhouse knowledge, which is in danger of being lost as senior staff retire and, often, are not being replaced. Multimedia systems will almost certainly be the next generation of commercial packages for the welding engineer, especially for training and marketing. Although relatively expensive to produce because of the time involved in designing screen displays (animations, graphics and video) and in discussions with technical experts, the packages should fulfil an increasing market need. Companies will use the packages for in-house training and training establishment will use the training programs for maintainig the quality and relevance of their courses. XIV In conclusion, computer based tehcnology in welding engineering is slowly maturing. The trend in recent years has been away from the production of speculative packages as aids to the welding engineer. Software houses appear to be concentrating on developing more company products. Succesfull products, especially databases and programs for complex calculations, are being progressively enhanced and integrated in response to the demands from industrial users for a more sophisticated product.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1996
Keywords: Bilgisayar destekli analiz; Kaynakçılık; MAG kaynak arkı; MIG kaynağı arkı; Maliyet analizi; Uzman sistemler; Computer aided analysis; Welding business; MAG welding; MIG welding arc; Cost analysis; Expert systems